UNDERSTANDING THE IMPACT OF INSTITUTIONAL FACTORS ON ASNAF SUSTAINABILITY: A PLS-SEM APPROACH - M Ashraf Al Haq; Norazlina Abd Wahab; Md. Mahmudul Alam (Bank Indonesia, 2021)
The study looked at the level of sustainable development, whether the institutional factors or often, the demographic changes over time, that might have an impact. The data was meticulously collected through 427 returned questionnaires among zakat recipients in eleven districts of Kedah, Malaysia, and it was thoroughly analysed using Partial Least Square – Structural Equation Modelling (PLS-SEM). This study found that the asnaf receives very minimum assistance and that can hardly empower them. Accordingly, it’s imperative that the fund needs to be geared towards long term productive use. The results support that the institutional contributory performance (ICP) having a positive effect, and the level of sustainable development of zakat recipients (SDZR) do increase after receiving zakat, but there are issues that need careful addressing. The study further examined the moderating role of demographic factors, such as earnings, age, marital status and gender, and witnessed that after zakat, all parameters improved, though individual moderating variables yet to show any significance. The study initiated a newer dimension through incorporating before-zakat and after-zakat scenarios in examining the comparative impact on SDZR, and likewise understanding the recipient’s level of Islamic self-actualisation.